UPAYA PENINGKATAN PENGETAHUAN MASYARAKAT TENTANG MAKANAN PENAMBAH STAMINA DAN IMUNITAS DI MASA PANDEMI COVID-19 - Isradji, Israhnanto; Yusuf, Iwang; Suparmi, Suparmi (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2022)
Currently, in the era of the covid-19 pandemic, to prevent the spreading of SARS-CORV2 infection, the public is advised to comply with health protocols and maintain stamina and immunity. Our community service activity (Pengabdian kepada Masyarakat/ PkM) was conducted to increase public knowledge, especially housewives to comply with health protocols and utilize traditional medicinal plants such as ginger, turmeric, and garlic to increase stamina and immunity. The knowledge improvement was evaluated by comparing the pre-test and post-test result using a questionnaire. Data was collected from 38 participants out of 50 participants who fulfilled the questioners. The T-paired test showed that the participant knowledge on covid-19 protocol and natural products for immune system was increased significantly (p<0.05). A 65.8% of participants understands the efforts to prevent the transmission of covid-19 “Protocol 5M” namely Wearing Masks, Washing Hands with Soap, Keeping Distance, Preventing Crowds, and Restricting Mobility. The awareness of participants on the benefit of herbal product to improve stamina and immunity was also improved. A training or workshop for participants in preparing healthy and safe food to avoid side effects can be considered for the next PkM activities.